1996
DOI: 10.1007/bf02249750
|View full text |Cite
|
Sign up to set email alerts
|

Case manager alliance with clients in an older cohort

Abstract: It was hypothesized that members of an older cohort of seriously mentally ill community mental health clients would develop stronger alliances with intensive case managers. Eighty-six clients participating in a study of case management services completed a measure of working alliance and structured interviews. It was found that older cohort clients, those age 45 or older, showed much stronger alliances with their case managers than younger clients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 29 publications
1
14
1
Order By: Relevance
“…Draine and Solomon (1996) reported that older clients formed a stronger alliance with their case managers than younger clients, but two studies (Calsyn, Morse, & Allen, 1999;Klinkenberg et al, 1998) found no relationship between age and the strength of the alliance. Gender had no impact on the strength of the case manager/client alliance in three previous studies (Calsyn et al, 1999;Klinkenberg et al, 1998Klinkenberg et al, , 2002.…”
Section: Client Characteristicsmentioning
confidence: 95%
“…Draine and Solomon (1996) reported that older clients formed a stronger alliance with their case managers than younger clients, but two studies (Calsyn, Morse, & Allen, 1999;Klinkenberg et al, 1998) found no relationship between age and the strength of the alliance. Gender had no impact on the strength of the case manager/client alliance in three previous studies (Calsyn et al, 1999;Klinkenberg et al, 1998Klinkenberg et al, , 2002.…”
Section: Client Characteristicsmentioning
confidence: 95%
“…While Neale and Rosenheck (1995) did not find correlations between consumer ratings of the alliance and consumer outcomes other than with satisfaction with the service, they did find that case manager ratings of the alliance were linked to consumers' improved global functioning, reduced symptom severity and improved community living skills. Some critics (Chinman et al, 2000) argue that alliance research is limited by the fact that it has gathered only quantitative data through retrospective, cross-sectional designs (see Draine & Solomon, 1996;Frank & Gunderson, 1990;Neale & Rosenheck, 1995;Solomon et al, 1995). These studies largely measured the alliance after consumers had been in case management for approximately 2 years (see Chinman et al, 2000 for an exception).…”
Section: Previous Research On the Working Alliancementioning
confidence: 95%
“…More recently, alliance investigations have extended to a range of community settings and populations, including addictions treatment (Connors, Carroll, DiClemente, Longabaugh, & Donovan, 1997); delinquent adolescents in community treatment (Florsheim, Shotorbani, Guest-Warnick, Barratt, & Hwang, 2000); and, low-income, latency aged children and their parents in family interventions within inner city schools (Toland, Hanish, McKay, & Dickey, 2002). Alliance assessment has also extended to adult intensive case management services (Chinman, Rosenheck, & Lam, 2000;Draine & Solomon, 1996;Klinkenberg, Calsyn, & Morse, 1998;Neale & Rosenheck, 1995;Solomon, Draine, & Delaney, 1995), demonstrating a positive link between the consumer's assessment of the alliance and some consumer outcomes, including treatment participation, subjective quality of life, and more positive attitudes about medication compliance (Alexander & Solomon, 2004;Solomon et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from its association with outcome, little is known about how the alliance varies between different psychiatric settings and diagnostic groups and how it is influenced by different mediating and moderating factors (26). Studies have indicated that a positive alliance is associated with less severe problems (5,7,(26)(27)(28), and age (28,29). As in psychotherapy research, there is a weak tendency that patients with borderline and other personality disorders have greater difficulties in establishing a good therapeutic alliance (21,28).…”
Section: Helping Alliance and Client Factors In Psychotherapeutic Andmentioning
confidence: 99%